Conexões políticas e subvenções governamentais nas companhias abertas do Brasil - Carlos Filho, Francisco de Assis (2020)
This study aimed to investigate the relationship between the receipt of government grants by companies listed on B3 and the existence of political connections. The argument of the thesis is that the government grants concessions in Brazil are in accordance with the assumptions of the theory of public choice, materialized in the trade offs known as political connections. The present study had a sample of 333 companies from the São Paulo stock exchange, Brazil, Bolsa, Balcão (B3) in the period 2014-2018, which satisfied the parameters of this research. Three regression models were tested: multiple linear regression, regression with robust models and quantile regression. Average comparison tests (t-test and ANOVA) and correlation tests were also performed. The data were obtained from four different databases: TSE, Explanatory Notes to DFPs, B3 and Economática®. The variables analyzed were: government grants, political connections, ROA, revenue growth, economic sector, size and indebtedness of companies. The main finding of this work was that the establishment of political connections is significant for the highest volume of resources received in the form of government grants and for the largest companies. In addition, important sectors for the development of the country are neglected by public entities when granting government subsidies in favor of sectors that have monopolies and are inserted in the public utility sector: Water and Sanitation and Electricity. As a consequence, it is concluded that government grants in Brazil do not fulfill their original purpose and serve to increase the economic and social distortions that are already so latent that they exist. The main limitation of this study is the variable political connections in the form of campaign financing, given the illegal practice of campaign financing via “slush fund”. As an opportunity for future research, we can mention new variables that explain the receipt of government grants, study of the new form of campaign financing, the “electoral fund” and the effects of possible tax reform on government grants. This research demonstrated that, as a public policy, the granting of government grants does not reach its objectives in the way that a society desires and is duly explained by the theory of public choice, which illustrates the failures of the State (Government) when it decides to carry out interventions.